Effect of Flammulina velutipes polysaccharides on the physicochemical properties of catfish surimi and myofibrillar protein oxidation during frozen storage - Ling, Liang; Liu, Ying; Zhang, Xin; Aziz, Tariq; Shahzad, Muhammad; Sameeh, Manal Y.; Wang, Ying; Cai, Chunbo; Zhu, Yingchun (Frontiers in Nutrition, 2023)
This work investigated the effect of Flammulina velutipes polysaccharides (FVP) on the myofibrillar protein (MP) oxidation protein and physicochemical properties of catfish surimi during the 75 d of frozen storage at -18 ℃. FVP was added to surimi at 1%, 1.5%, and 2%, respectively, the degree of MP oxidation and the physicochemical properties of the surimi were investigated, and the microstructure of the surimi was observed by scanning electron microscopy (SEM). The results showed that the carbonyl content and the thiobarbituric acid reactants (TBARS) in the FVP groups were lower than that in the CK group (the blank surimi). In comparison, the total sulfhydryl content, the solubility and Ca 2+ -ATPase activity were higher than that in the CK group after 75 d storage. The addition of FVP significantly increased the water-holding capacity (WHC), gel strength, elastic modulus (G'), and loss modulus (G") of surimi, and made the gel of surimi stronger continuity and denser structure. Therefore, FVP has a better cryoprotective effect on surimi. It improves the quality of surimi, slows down the oxidation of MP and lipid and water loss during frozen storage. The antifreezing effect of FVP added at 2% was similar to that of commercial protectants (4% sucrose and 4% sorbitol).